Targeted Fisetin-Encapsulated β-Cyclodextrin Nanosponges for Breast Cancer - Alaa R. Aboushanab; Riham M. El-Moslemany; Amal H. El-Kamel; Radwa A. Mehanna; Basant A. Bakr; Asmaa A. Ashour (MDPI AG, 2023)
Fisetin (FS) is considered a safer phytomedicine alternative to conventional chemotherapeutics for breast cancer treatment. Despite its surpassing therapeutic potential, its clinical utility is hampered by its low systemic bioavailability. Accordingly, as far as we are aware, this is the first study to develop lactoferrin-coated FS-loaded β-cyclodextrin nanosponges (LF-FS-NS) for targeted FS delivery to breast cancer. NS formation through cross-linking of β-cyclodextrin by diphenyl carbonate was confirmed by FTIR and XRD. The selected LF-FS-NS showed good colloidal properties (size 52.7 ± 7.2 nm, PDI < 0.3, and ζ-potential 24 mV), high loading efficiency (96 ± 0.3%), and sustained drug release of 26 % after 24 h. Morphological examination using SEM revealed the mesoporous spherical structure of the prepared nanosponges with a pore diameter of ~30 nm, which was further confirmed by surface area measurement. Additionally, LF-FS-NS enhanced FS oral and IP bioavailability (2.5- and 3.2-fold, respectively) compared to FS suspension in rats. Antitumor efficacy evaluation in vitro on MDA-MB-231 cells and in vivo on an Ehrlich ascites mouse model demonstrated significantly higher activity and targetability of LF-FS-NS (30 mg/kg) compared to the free drug and uncoated formulation. Consequently, LF-FS-NS could be addressed as a promising formulation for the effective management of breast cancer.